Effect of Fiber Orientation on the Mechanical Performance of Polyester/Fiberglass Composites Fabricated by VARI - Agita Phasa; Oji Kuncoro Darma Putra; Wahyu Solafide Sipahutar; Istiara Rizqillah Hanifah (Jurnal Permadi : Perancangan, Manufaktur, Material dan Energi, 2025)
The fiber orientation in polyester/fiberglass composites fabricated using the Vacuum Assisted Resin Infusion (VARI) method was investigated. Three different fiber orientation configurations consisting of three woven layers were used: 0°/45°/0°, 45°/45°/45°, and 45°/0°/45°. Tensile and flexural tests were conducted to evaluate the strength, strain, and flexural modulus of each specimen. The results demonstrated that fiber orientation has a significant impact on mechanical performance. The 0°/45°/0° specimen exhibited the highest tensile strength of 164.66 MPa and flexural strength of 1091.17 MPa. In contrast, the 45°/45°/45° specimen showed the lowest tensile strength of 58.57 MPa, while the 45°/0°/45° specimen had the lowest flexural strength of 772.97 MPa. The 45°/45°/45° configuration displayed intermediate mechanical values with a more homogeneous stress distribution. Interestingly, the highest flexural modulus, 5702.23 MPa, was obtained from the 45°/0°/45° specimen, indicating high stiffness despite limited deformation. These findings confirm that proper selection of fiber orientation plays a crucial role in designing composites with an optimal balance of strength, stiffness, and ductility.